Job Performance Evaluation of Medical Social Workers during Covid-19 Crisis: Tasks, Attitudes, and Difficulties - Walaa Elsayed (Emerging Science Journal, 2023)
Objectives: The objective of this study is to evaluate the job performance efficiency of social workers in medical institutions during the COVID-19 pandemic crisis, based on three factors "job tasks, attitudes of co-workers, and difficulties" faced by social workers in performing their duties. Methods/Analysis: This study is a descriptive-analytical study. A comprehensive social survey approach was used to collect data from 54 social workers in isolation hospitals for coronavirus patients. A questionnaire was employed to gather the required data. The collected data were analyzed using weight analysis to determine the value and weighted relative weight of job performance efficiency. Findings: The results of the study showed that the job performance efficiency of social workers in medical institutions during the COVID-19 pandemic crisis was at a middle level, with a total weight of 3611 and a weighted relative weight of 55.7%. Moreover, the study found statistically significant differences in the degree of job performance efficiency according to gender, age, educational qualification, number of experience years, and number of training courses at a 5% significance level. Novelty/Improvement:The study recommends the development of the knowledge and skills of medical social workers through training courses on how to deal with global health crises and disasters. Additionally, reducing the administrative burdens on medical social workers is important, as these burdens restrict their role and limit their ability to perform their tasks with the medical team. Doi: 10.28991/ESJ-2023-07-04-08 Full Text: PDF